L‐Dex, arm volume, and symptom trajectories 24 months after breast cancer surgery. (1st June 2020) - Ridner, Sheila H.; Shah, Chirag; Boyages, John; Koelmeyer, Louise; Ajkay, Nicolas; DeSnyder, Sarah M.; McLaughlin, Sarah A.; Dietrich, Mary S.
Abstract: Purpose: Study objectives were to examine: (a) biomarker trajectories (change from presurgical baseline values of Lymphedema index (L‐Dex) units and arm volume difference) and symptom cluster scores 24 months after breast cancer surgery and (b) associations of these objective biomarkers and symptom cluster scores. Patient/treatment characteristics influencing trajectories were also evaluated. Methods: A secondary analysis of data from the published interim analysis of a randomized parent study was undertaken using trajectory analysis. Five hundred and eight participants included in the prior analysis with 24 months of postsurgical follow‐up were initially measured with bioelectric impedance spectroscopy (BIS) and tape measure (TM) and completed self‐report measures. Patients were reassessed postsurgery for continuing eligibility and then randomized to either BIS or TM groups and measured along with self‐report data at regular and optional* visits 3, 6, 12, 15*, 18, 21*, and 24‐months. Results: Three subclinical trajectories were identified for each biomarker (decreasing, stable, increasing) and symptom cluster scores (stable, slight increase/decrease, increasing). Subclinical lymphedema was identified throughout the 24‐month period by each biomarker. An L‐Dex increase at 15 months in the BIS group was noted. The self‐report sets demonstrated contingency coefficients of 0.20 (LSIDS‐A soft tissue, P  = .031) and 0.19 (FACTB+4, P  = .044) with the L‐Dex unit change trajectories. Conclusions: These data support the need for long‐term (24 months) prospective surveillance with frequent assessments (every 3 months) at least 15 months after surgery. Statistically significant convergence of symptom cluster scores with L‐Dex unit change supports BIS as beneficial in the early identification of subclinical lymphedema. Abstract : Long‐term (24 months) lymphedema prospective surveillance with frequent assessments (every 3 months) at least through 15‐months post‐surgery is indicated. Convergence of symptom cluster scores with L‐Dex unit change supports Bioelectric Impedance Spectroscopy as beneficial in the early identification of sub‐clinical lymphedema.